2015
DOI: 10.1007/s10854-015-3149-2
|View full text |Cite
|
Sign up to set email alerts
|

Damage recovery of FIB modified Si for directed-assembly of semiconductor nanostructures

Abstract: Focused ion beam (FIB) techniques have previously been shown to have applications in templating semiconductor nanostructure growth on Si. To assess crystalline quality in this method, or in other FIB-based nano-fabrication methods in Si, we assess in this work FIBimplantation damage in Si and subsequent recovery by annealing. Specifically, we study Si substrates implanted to 1 9 10 12 -5 9 10 15 ions cm -2 fluences of 30 kV Si 2? , Ge 2? and Ga ? incident normally at room temperature, covering a structural dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…3(b) . The central recovered regions are relatively defect free, in agreement with the damage recovery measured with Raman spectroscopy on annealing Si substrates rendered amorphous by a focused Si 2+ ion beam 36 , 37 . These data confirm that Si 2+ implantation at doses relevant to quantum dot patterning, followed by heating to the temperature required for nanostructure growth, can result in defect-free regions beneath the grown nanostructure but with defects around the perimeter of the implanted area.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…3(b) . The central recovered regions are relatively defect free, in agreement with the damage recovery measured with Raman spectroscopy on annealing Si substrates rendered amorphous by a focused Si 2+ ion beam 36 , 37 . These data confirm that Si 2+ implantation at doses relevant to quantum dot patterning, followed by heating to the temperature required for nanostructure growth, can result in defect-free regions beneath the grown nanostructure but with defects around the perimeter of the implanted area.…”
Section: Resultssupporting
confidence: 81%
“…As mentioned above, compared to Ga + , the higher dose required for Si 2+ patterning and the longer implantation range of Si 2+ means that greater amorphization of the substrate 36 is expected during implantation. The heat treatment that is part of the Ge quantum dot growth needs to recover this damage if we are to optimize the electronic properties of the resulting nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…For a dose > 10 14 cm −2 , the PMOR signal starts to saturate. This saturation has been observed for Si damaged with Au, Kr, Ar, Si, Ge and Ga [24,25] using a similar dose, and is referred to as the dose required for partial amorphization. As observed in Fig.…”
Section: Impact Of Fib Damage and Amorphization On The Optical Properties Of Bulk Semiconductorsmentioning
confidence: 72%
“…This process has been studied extensively in the field of ion implantation [23] and shown that a minimum dose is required to form a fully amorphized layer. Full amorphization is both energy-and mass-dependent, but typically requires a dose in the range 10 14 −10 15 cm −2 [24,25] .…”
Section: Ion Beam Damage In a Semiconducting Specimenmentioning
confidence: 99%
“…Additional measurement details are provided elsewhere. 16 Errors for D in this work are derived from the sum of the standard deviations in the measurements of H and H 0 normalized to the average value of H 0 . Error in the c-Si peak shift measurements at a given fluence is the standard deviation in the peak shift measurements.…”
Section: Methodsmentioning
confidence: 99%